2018
DOI: 10.1007/s10388-018-0630-z
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative enteral supplementation with glutamine, fiber, and oligosaccharide reduces early postoperative surgical stress following esophagectomy for esophageal cancer

Abstract: Perioperative use of enteral supplementation with glutamine, fiber, and oligosaccharide likely contributes to a reduction in early surgical stress after an esophagectomy. These beneficial effects can bring about early recovery from postoperative immunosuppressive conditions after radical esophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The thoracotomy was found to be able to cause intense stress responses proportionate to both visceral damage and skin incision pain. 19 Previous study found that wound infiltration with local anesthetics could block parietal afferent signals from incision injury. 20 However, it was deemed to have weak inhibiting effect on the afferent noxious stimuli from visceral pain caused by surgical operation.…”
Section: Discussionmentioning
confidence: 99%
“…The thoracotomy was found to be able to cause intense stress responses proportionate to both visceral damage and skin incision pain. 19 Previous study found that wound infiltration with local anesthetics could block parietal afferent signals from incision injury. 20 However, it was deemed to have weak inhibiting effect on the afferent noxious stimuli from visceral pain caused by surgical operation.…”
Section: Discussionmentioning
confidence: 99%
“…Details of perioperative management have been described previously. 21 An immune-enhancing diet (IMPACT Ò ) was given orally for 5 days before surgery. After surgery, patients were extubated in the operating room.…”
Section: Surgical Procedures and Perioperative Managementmentioning
confidence: 99%
“…14 Therefore, some researchers suggest that patients with severe brain injury should be given supplementary glutamine at an early stage. [15][16][17] Studies have discovered that both glutamine and lowdose amino acids have the potential to activate autophagy. 18 Besides, the effect of autophagy explains that preserving (or minimizing) early nutrition may be more beneficial to critically ill patients.…”
Section: Discussionmentioning
confidence: 99%